Palestinian labour migration to Israel : labour, land and occupation - Farsakh, Leila (Political economy of the Middle East and North Africa., 2005)
This book examines the flow of Palestinian labour to Israel over the last three decades, and shows how it has fluctuated over time, with, most recently, a shift in the flow towards Israeli settlements in the occupied territories.